2006
DOI: 10.1088/0953-8984/18/10/006
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of anisotropic phonon systems in superfluid helium

Abstract: The thermodynamic functions of anisotropic phonon systems in superfluid helium are calculated for all levels of anisotropy. The results show that the thermodynamic functions of strongly anisotropic phonon systems are essentially different from isotropic ones. It is shown that for strongly anisotropic phonon systems, in thermodynamic equilibrium, the energy density of high-energy phonons, ε/kB≥10 K, is more than ten times higher than in a cone with the same total energy density and with the Bose–Einstein distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Figure 3 shows the angular dependences of the amplitudes T c / ͑Tṽ n ͒, P / ͑cṽ n ͒, and ṽ s / ͑ṽ n ͒ calculated from Eqs. ͑24͒-͑26͒, for w / c = 0.97 and T = 0.05 K, which we estimate 11,12 as the typical values in experiments. 3,4,7,8 We see that a strongly anisotropic phonon system in superfluid helium, where w Ϸ c, which can be created in experiments, 3,4,7,8 is a favorable experimental system for observing and studying the transverse mode.…”
Section: Transverse Modes In a Phonon Systemmentioning
confidence: 56%
See 2 more Smart Citations
“…Figure 3 shows the angular dependences of the amplitudes T c / ͑Tṽ n ͒, P / ͑cṽ n ͒, and ṽ s / ͑ṽ n ͒ calculated from Eqs. ͑24͒-͑26͒, for w / c = 0.97 and T = 0.05 K, which we estimate 11,12 as the typical values in experiments. 3,4,7,8 We see that a strongly anisotropic phonon system in superfluid helium, where w Ϸ c, which can be created in experiments, 3,4,7,8 is a favorable experimental system for observing and studying the transverse mode.…”
Section: Transverse Modes In a Phonon Systemmentioning
confidence: 56%
“…12 we have shown that for the phonon pulses, the critical velocity is very close to the Landau critical velocity, which is equal to the first sound velocity c for pure phonon system. Direct experiments 3,4,7,8 show that the phonon pulse, injected into superfluid helium, moves through it with the velocity close to c. This means that the phonon pulse has a counterflow velocity w, with a value close to the Landau critical velocity c.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…In particular, it was shown theoretically using general relations that quasiparticle systems, with large values of w close to the sound velocity, are thermodynamically stable, 2 and that they possess unique thermodynamic properties. 4,5 These points are discussed in detail at the beginning of Sec. V.…”
Section: Introductionmentioning
confidence: 98%
“…11 The pulse of low-energy phonons, or equivalently a small volume of normal fluid, moves through the superfluid with a velocity almost exactly equal to the sound velocity. 12 This is the maximum velocity that a normal fluid of only phonons can have, [13][14][15][16] and it is much higher than the usual critical velocity for a normal fluid with rotons, i.e., the Landau criti-cal velocity. The superfluid is very nearly stationary with respect to the experimental cell.…”
Section: Introductionmentioning
confidence: 96%